Organologi dan Fungsi Sape dalam Ritual Panen Raya Dayak Kayan Kalimantan Utara - Musa Kiring (Faculty of Languages and Arts, Universitas Negeri Padang, 2023)
This article aims to provide understanding and knowledge to the younger generation about the organology and function of Sape music used in the Dayak Kayan harvest ritual in North Kalimantan. This research uses a qualitative descriptive research method with data collection techniques through observation, interviews and documentation steps. Observations were carried out on the Kayan tribe in Naha Aya Village, Peso Hilir District, Bulungan Regency, North Kalimantan. To analyze the results of this research, the researcher carried out data reduction, then the data was presented in the form of descriptions and images, and finally concluded. The results of the research explain that the organology of the Sape music used in the harvest ritual is Sape with 3 strings and was studied in terms of organology, how to make it and how to play the stringed musical instrument. Apart from that, Sape music has a role and function in the Dayak community's harvest rituals, including: 1) functioning as a medium for religious rituals; 2) functions as an entertainment medium, as a dance accompaniment medium, 3) functions as a communication medium, 4) functions as a self-expression, 5) functions as an economic means, and 6) functions as a symbolic offering. By providing understanding and knowledge to the younger generation regarding the form and function of Sape music in harvest rituals, it is hoped that the younger generation will preserve and preserve traditional Sape music.